Adaptation to Extreme Environments in an Admixed Human Population from the Atacama Desert. (6th August 2019) - Vicuña, Lucas; Fernandez, Mario I; Vial, Cecilia; Valdebenito, Patricio; Chaparro, Eduardo; Espinoza, Karena; Ziegler, Annemarie; Bustamante, Alberto; Eyheramendy, Susana
Abstract: Inorganic arsenic (As) is a toxic xenobiotic and carcinogen associated with severe health conditions. The urban population from the Atacama Desert in northern Chile was exposed to extremely high As levels (up to 600 µg/l) in drinking water between 1958 and 1971, leading to increased incidence of urinary bladder cancer (BC), skin cancer, kidney cancer, and coronary thrombosis decades later. Besides, the Andean Native-American ancestors of the Atacama population were previously exposed for millennia to elevated As levels in water (∼120 µg/l) for at least 5, 000 years, suggesting adaptation to this selective pressure. Here, we performed two genome-wide selection tests—PBS n 1 and an ancestry-enrichment test—in an admixed population from Atacama, to identify adaptation signatures to As exposure acquired before and after admixture with Europeans, respectively. The top second variant selected by PBS n 1 was associated with LCE4A-C1orf68, a gene that may be involved in the immune barrier of the epithelium during BC. We performed association tests between the top PBS n 1 hits and BC occurrence in our population. The strongest association ( P  =   0.012) was achieved by the LCE4A-C1orf68 variant. The ancestry-enrichment test detected highly significant signals ( P  =   1.3 × 10 −9 ) mapping MAK16, a gene with important roles in ribosome biogenesis during the G1 phase of the cell cycle. Our results contribute to a better understanding of the genetic factors involved in adaptation to the pathophysiological consequences of As exposure.